Human-Centric AI Sebagai Strategi Kepemimpin dalam Mengatasi AI Anxiety pada Karyawan - Saskia Husnun Nisa; Wasiatur Rizqiyyah; Gadis Syarafina Putri Azwin; Mochammad Isa Anshori (Institut Nalanda, 2026)
Artificial Intelligence (AI)-based digital transformation has transformed organizational practices, particularly in decision-making and operational efficiency. However, the adoption of AI has also given rise to a phenomenon known as AI anxiety, referring to employees’ concerns about the potential replacement of human roles by automation technologies. This study aims to analyze the relationship between AI implementation, employee technology-related anxiety, and the role of the human-centric AI approach in addressing these dynamics. The method employed is a systematic literature review of relevant scholarly articles published within the last five years, focusing on digital leadership, technostress, and human–AI collaboration. The findings indicate that the success of AI implementation is determined not only by technological capabilities but also by leadership strategies that prioritize human values. The human-centric AI approach can reduce employee anxiety by enhancing transparency, strengthening digital competencies, and creating adaptive work environments. This study contributes to the development of management literature by emphasizing the integration of AI technologies with human values in modern leadership practices.